2018
DOI: 10.1111/jan.13859
|View full text |Cite
|
Sign up to set email alerts
|

Napping on night‐shifts among nursing staff: A mixed‐methods systematic review

Abstract: Although research on this topic has just started, napping during night-shift is beneficial to nurses' health and performance. Research should further explore the long-term impact on of night-shift napping on nurses, people and organization using sound methodological designs. Managers should actively develop strategies to address night-shift napping barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 68 publications
0
32
0
Order By: Relevance
“…This prolongation of work time can leave nurses with less time to relax and recharge, which impedes the timely reduction of fatigue. As for night shifts, it is well accepted that working at night requires a lot of energy and is more likely to lead to the disorder of body rhythms, which may have a serious impact on fatigue of nurses 43. In addition, we found nearly 20% of nurses were highly dissatisfied with the nurse–patient relationship.…”
Section: Discussionmentioning
confidence: 68%
“…This prolongation of work time can leave nurses with less time to relax and recharge, which impedes the timely reduction of fatigue. As for night shifts, it is well accepted that working at night requires a lot of energy and is more likely to lead to the disorder of body rhythms, which may have a serious impact on fatigue of nurses 43. In addition, we found nearly 20% of nurses were highly dissatisfied with the nurse–patient relationship.…”
Section: Discussionmentioning
confidence: 68%
“…This study's findings suggest that the development of strategies that reward night shift work may help lower the psychological effects on the nurses who are involved in the shift work. A systematic review by Li et al suggested that the integration of napping during a night shift is beneficial to nurses' health, their psychomotor vigilance and their performance [33].…”
Section: Discussionmentioning
confidence: 99%
“…According to recent estimates, 21% of the European Union workforce is employed in a nonstandard work schedule (Parent-Thirion et al, 2017). Since hospitals operate around the clock, nursing staff works continuous working schedules (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some have focused on spontaneous napping (de Castro Palermo et al, 2015;Silva-Costa et al, 2017), while others have compared nap settings (Centofanti et al, 2016;Davy and Göbel, 2018). Though the merits of napping remain controversial (e.g., sleep inertia after a nap), Ruggiero and Redeker (2014) and Li et al (2019) have recently reported on the beneficial effects of napping among nurses (Li et al, 2019). Differences in nap outcomes may result from the assessment methods: most studies have relied on self-report questionnaires and subjective assessment of sleep behavior and alertness after a nap (de Castro Palermo et al, 2015;Rotenberg et al, 2016;Davy and Göbel, 2018;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation